A Analisis Kinerja Keuangan Dalam meningkatkan Nilai Perusahaan - Dewi Oktayani; Lukman Hakim; Susilawati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to analyze the effect of Return on Assets, Return On Equity anda Deb to Equity Ratio on the value of LQ45 companies listed on the Indonesia Stock Exchange 2014-2018. When the research was conducted in November-December 2020. The data used in this study are secondary data in the form of datafrom the companies 2014-2018 financial statemens obtained from Indonesia stock exchange. The research population is LQ45 companies listed on the Indo-nesia stock exchange (IDX) from 2014-2018. The sample of this research is 13 companies, the sampling technique uses purposive sampling method and that meets the sample selection criteria. The data analysis technique uses Multiple Regresision Test. Retur on asset has a positive and significant effect on firm value. Return On Equity Has no Significant and Positive Effect on Firm Value. Debt to Equity Ratio has a significant and positive effect on firm value